2015
DOI: 10.1161/strokeaha.114.007847
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Imaging Abnormalities and Cognition

Abstract: Background and Purpose The relationships between cerebrovascular lesions visible on imaging and cognition are complex. We explored the possibility that cerebral cortical volume mediated the relationship. Methods 1906 non-demented participants (59% women; 25% African-American; mean age 76.6 years) in the Atherosclerosis Risk in Communities (ARIC) study underwent cognitive assessments, risk factor assessments, and quantitative MR imaging for white matter hyperintensities (WMH) and infarcts. The Freesurfer imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
106
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 60 publications
6
106
2
Order By: Relevance
“…Among our brain MRI findings, the strongest associations with diabetes appeared in measures of brain atrophy, including sulcal widening, ventricle enlargement, and reduced overall brain volume. Similar associations have been reported in several other studies [35][36][37][38][39][40][41], including studies of middle-aged African Americans [41,42] and Asians [43,44]. The underlying mechanism remains unclear, but in addition to microvascular disease, both hydration status and direct neurodegeneration might be involved [45,46].…”
Section: Discussionsupporting
confidence: 85%
“…Among our brain MRI findings, the strongest associations with diabetes appeared in measures of brain atrophy, including sulcal widening, ventricle enlargement, and reduced overall brain volume. Similar associations have been reported in several other studies [35][36][37][38][39][40][41], including studies of middle-aged African Americans [41,42] and Asians [43,44]. The underlying mechanism remains unclear, but in addition to microvascular disease, both hydration status and direct neurodegeneration might be involved [45,46].…”
Section: Discussionsupporting
confidence: 85%
“…Although there have been consistent corpus callosum/vascular risk findings in the literature, the anterior part (genu) of the corpus callosum may be most susceptible to vascular disease effects due to its small diameter or thin fibers compared to the posterior part (splenium) of the corpus callosum, where the fibers are larger in diameter. In addition, frontal lobes appear to be more susceptible to cerebrovascular disease, have greater burden of WM lesions, and are also a convergence point for several brain connections,6, 32, 49 supporting the use of genu FA as the cerebrovascular biomarker.…”
Section: Discussionmentioning
confidence: 96%
“…Because the accumulation of chronic conditions (in this study, worsening vascular health) has been equated to accelerated aging, these results are as expected. There is evidence supporting the association between increased vascular risk and atrophy in regions vulnerable to AD 7, 32, 33, 34. Given that the associations of systemic vascular health and AD with sMRI are observed in the same regions, sMRI does not qualify as an independent prodromal biomarker for cerebrovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that decline in vascular health has a significant impact on brain health and also increases the risk of AD dementia 39 . While it is well known that the impact of vascular health on cognitive performance is mediated via vascular brain injury 6, 8 , the direct impact of vascular health on each individual ADP process, namely amyloid, tau, and AD-associated neurodegeneration, is poorly understood and the interrelationships between ADP and vascular health are highly debated.…”
Section: Introductionmentioning
confidence: 99%